The Effect of Spontaneous Group Discussion in Speaking Skill to Senior High School Students - Wiratno, Wiratno; Huda, M. Alimul (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
This article discusses the impact of implementing Spontaneous Group Discussion (SGD) in a senior high school experimental class. Challenges during speaking practice in the classroom lead to the students having reduced motivation to speak English. SGD is suggested as a way to address this issue by evaluating its efficacy in comparison to a traditional approach. This research employs a quasi-experimental design with pretest and post-test assessments. The analysis showed the result of this research that F (2,85) = 26.591, P 0.000 < 0.05. From the result a notable difference emerged between the experimental and control groups, resulting in the dismissal of the null hypothesis which posited that both strategies (SGD technique and GTM) are identical. Research findings indicate that SGD is more efficient for learning speech, allowing students to rapidly grasp important lessons related to the teacher's chosen topic. Hence, teachers may find value in using the findings of this research when instructing students on English speaking skills.